Advancing preparedness for clinical research during infectious disease epidemics. Issue 2 (20th May 2019) - Gobat, Nina; Amuasi, John; Yazdanpanah, Yazdan; Sigfid, Louise; Davies, Hugh; Byrne, John-Paul; Carson, Gail; Butler, Christopher; Nichol, Alistair; Goossens, Herman
The Spanish Flu of 1918 reached every continent, infected one-third of the world's population and claimed over 50 million lives [1]. The centenary of this event presented a stark reminder of the threat of infectious disease epidemics to global health and security. These threats persist, fuelled in part by features of modern-day living such as climate change, globalisation, deforestation and population growth [2]. While progress has been made for managing infectious disease epidemics, critical gaps in leadership, governance, coordination and finance remain [3]. Clinical research is vital for an effective response to infectious disease epidemics. To be viable, preparations must be made in anticipation of infectious disease epidemics and must address barriers to rapid deployment and implementation. bit.ly/2IzUlyv